Azitromicina inibe a infecção por Toxoplasma gondii em oculares de fetos e reduz o parasitismo na infecção congênita e adquirida em modelo experimental de Calomys callosus - Lopes, Carla Duque (2008)
Toxoplasma gondii is an obligatory intracelullar parasite of large geographical distribution that causes severe sequelae to fetuses of mothers infected for the first time during pregnancy and in immunossuppressed adults. The drugs most frequently used for the treatment of toxoplasmosis are a combination of sulfadiazine and pirimethamine plus folinic acid. However, these drugs present severe side effects and currently their efficacy is under study. Other medicines that are considered as alternatives for the treatment are clindamycin, atovaquone and azithromycin. The latter has demonstrated to be effective againts both tachyzoites and bradyzoites in vitro with lesser side effects in clinical practice. In this study we tested the efficacy of azithromycin on the reduction of vertical transmission of Toxoplasma, by the analyses of fetal eyes of Calomys callosus, as well as the acquired adult infection analyzing brains of the mothers and adult males. For the analysis of the treatment on the vertical transmission, females of C. callosus were inoculated perorally with 20 cysts of the ME49 strain of T. gondii on the first day of pregnancy and then received the different treatments. Fetuses and mothers brains were collected on days 15, 17 e 19 of gestation/infection. Females were sorted into three treatment groups: control (vehicle), azithromycin (300mg/kg/dia) and the association of the drugs sulfadiazine (100 or 75 mg/Kg/day), pyrimethamine (100 or 50mg/Kg/day) and folinic acid (15mg/Kg/day). The drugs were administered orally starting at different days post-infection and animals were bled on the first day of pregnancy and on the day of sacrifice to perform ELISA tests for the detection of anti-T. gondii antibodies. For the analyses of acquired infection, adult males were infected and treated using the same drugs as the females, for either the same or longer periods. After treatment, animals were sacrificed and the brains were collected from the adults and eyes from the fetuses. All samples were processed for immunohistochemistry, using a policlonal antibody against T.gondii , while one of the eyes of fetuses from day 19 were also processed for real time PCR detection of parasite DNA. Parasite load was significantly reduced in brain tissues of females treated with azithromycin when compared to SPAf treatment. In fetuses of azithromycin-treated mothers no parasites were detected in the eyes analyzed. No difference was seen in parasite load when the SPAf-treated group was compared to the control group. In brain tissues of adult males, there was significant reduction in parasite numbers in the azithromycin-treated animals. Our study demonstrated a good efficacy of azithromycin for the treatment of pregnant females, diminishing fetal ocular infection, as well as for the treatment of adult animals, representing an alternative choice for the treatment of toxoplasmosis.